Development and Validation of a Scale for Measuring Internal Auditing Effectiveness in Tunisian Companies - Dellai, Hella; Slimene, Nadia (International Journal of Advanced Engineering, Management and Science, 2021)
The purpose of the current study is to develop and validate a multidimensional scale for measuring internal auditing effectiveness (IAE) in Tunisia. The authors’ methodological approach is based on both qualitative and quantitative methodologies. The qualitative technique was used to generate scale items to measure IAE and the quantitative technique was utilised to test and validate the scale. The sample includes 148 chief internal auditors from Tunisian companies. Data were divided in half. First half was utilised for exploratory factor analysis (EFA) and the second half of the data were utilised to run confirmatory factor analysis (CFA). The study found that IAE is a three-dimensional construct (internal audit process, output of internal audit and impact of internal audit) which is consisted of 16 items. This reliable and valid scale offers a practical instrument to measure IAE that very interesting to managers and external auditors.